Implementation of the West Sumatra Provincial Election Commission's Voter Education Program Following the 2024 General Election - Ismi Rahmadani; Adil Mubarak (Journal of Management and Social Sciences, 2026)
Voter education has become an essential strategy for strengthening political awareness and democratic participation, particularly among young and first-time voters. Research specifically addressing post-election voter education implemented by provincial election management bodies remains limited. This study aims to analyze the implementation of the voter education program conducted by the West Sumatra Provincial Election Commission after the 2024 General Election and to identify the supporting and inhibiting factors affecting its implementation. A qualitative approach with a descriptive design was employed, involving election commissioners, institutional partners, and university students selected through purposive and snowball sampling. Data were collected through in-depth interviews and documentation studies and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the program was implemented through public outreach, webinars, public lectures, university partnerships, the establishment of Saka Pramuka Rintisan Yogaswara, and social media utilization. Viewed from Edward III’s policy implementation framework, communication, resources, disposition, and bureaucratic structure influenced program implementation. The study concludes that sustainable voter education is crucial for improving political literacy and recommends stronger digital communication, wider institutional collaboration, and continuous youth-oriented voter education programs.